Association Between Nutritional Status and Phisical Activity at School in Chilean Children 4 to 14 Years [Asociación Entre Estado Nutricional y Tiempo de Actividad Física Escolar de Niños y Niñas Chilenos de 4 a 14 Años] - Herrera-Valenzuela, T (Sociedad espanola de dietetica, 2014)
Introduction: High levels of physical inactivity and overweight childrens Chileans require the study variables linking BMI with other factors to benefit the health of the school population. Objective: To determine the association between nutritional status, age and physical activity time school children (NE) of a private school in Temuco, Chile. Methods: The research provides a non-experimental, descriptive correlational, cross design with a quantitative approach. The sample included 595 subjects (292 women), between 4 and 14 years (8.1 ± 3.0 years) who were evaluated anthropometric and counted the hours of physical education and attendance at workshops of physical activity. Results: NE hold 43.8% of overweight and obesity. Regarding physical activity while 38% practice two to three hours per week, 32% four to five and 30% six to seven. Contents ? 5 hours/week and attend workshops of physical activity are protective factors for obesity OR = 0.45 (95% CI 021 to 0.96, P <0.05) and OR = 0.23 (0.10 to 0, 51, p <0.01) respectively. Conclusion: NE with a normal nutritional status are those who spend more time engaging in physical activity at school, while overweight and obese schoolchildren have less time. Moreover, a decrease in physical activity of NE as age increases is observed, which could affect their future nutritional status.